Training, anthropometrics and performance relationships in French male swimmers of three age categories for 200 m events - Hellard, P.; Caudal, N.; Avalos, M.; Knopp, M.; Chatard, J. C. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION Though a great number of studies have dealt with the technical, bioenergetic, and anthropometric changes over the period associated with children's growth, (Malina, 1994) little research has examined the evolution of kinematics parameters during this development period. The aim of the present study is to investigate kinematics race parameters over an 8 year period for French male swimmers taking into account a) Training content and b) Anthropometric development. METHODS Performance kinematics parameters, training variables and anthropometric characteristics were studied for 163 male swimmers grouped in three categories C1 (14-15 years old), C2 (16-17 years old), C3 (18-19 years old). For the 200 m events the 4 strokes velocities, stroke frequency, stroke length, and turn velocities were calculated using a specific competition analysis computer program. Self-reported training questionnaires were completed during the month preceding the French National Age Group Championships. For each swimmer involved their average weekly training session volume, average weekly distance, annual distance and average weekly volume of dry-land sessions were quantified. During the competition week, the height, weight, foot size and arm span were measured for each swimmer. In order to take account of the complex non-linear relationships between variables neural network technique was applied to data and compared to stepwise regression. RESULTS Performance increased between C1 and C2 (p £ 0.05), and between C2 and C3 (Ns). Compared to C1, C3 was characterised by higher stroke rate in butterfly and backstroke and greater stroke length in breastroke and freestyle events (p £ 0.05). Anthropometric characteristics increased significantly from C1 to C3 (p £ 0.05). Training was significantly higher (p ) 05.0 £ between C1 and C2 and stabilized then. Neural network fitted data significantly (r_=0.62 p ) 01.0 £ . DISCUSSION Male performances over the stages of the 200 m events improved during puberty. The development of technical performance characteristics was a different function of biomechanical characteristics and the different swimming styles. The observed inter-relationships between anthropometric growth, training and competitions warrant the suggestion that there should be an optimum balance between these factors in order to optimize performance.